2010
DOI: 10.1007/s10443-010-9126-2
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Mechanical Properties of 3D Four-Directional Rectangular Braided Composites Part 1: Microgeometry and 3D Finite Element Model

Abstract: Based on the microstructure of three-dimensional (3D) four-directional rectangular braided composites, a new parameterized 3D finite element model (FEM) is established. This model precisely simulates the spatial configuration of the braiding yarns and considers the cross-section deformation as well as the surface contact due to the mutual squeezing in the braiding process. Moreover, it is oriented in the same reference frame as the composites, which coincides with the actual configuration of 3D braided composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 10 publications
(10 reference statements)
2
26
0
Order By: Relevance
“…Fang et al studied the progressive damage and nonlinear behaviors of 3D braided composite under unidirectional tension. Li et al discussed the mechanical properties of 3D four‐directional rectangular braided composite from its micro‐geometry and 3D finite element model. Jiang et al predicted the mechanical properties of 3D braided composites using a helix geometry model.…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al studied the progressive damage and nonlinear behaviors of 3D braided composite under unidirectional tension. Li et al discussed the mechanical properties of 3D four‐directional rectangular braided composite from its micro‐geometry and 3D finite element model. Jiang et al predicted the mechanical properties of 3D braided composites using a helix geometry model.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on the mechanical properties of 3D braided composites have been made, including the establishment of structural models [1][2][3][4], the prediction of stiffness and strength properties [5][6][7][8][9], and the investigation of damage and failure mechanisms under various loadings [10][11][12][13][14][15]. In these micromechanical analysis works, only two constituents: the braiding yarn and matrix have been considered while the interface has been ignored.…”
mentioning
confidence: 99%
“…the fiber and the matrix. Li et al [13] developed a new finite element model based on the microstructure of 3-D four-directional braided composites and observed that the braiding angle is an important parameter, which affects the external dimension, braiding pitch length, and fiber volume fraction of 3-D braided composites. Dong and Feng [14] studied the strength and failure pattern of 3-D braided composites by simulating the damage propagation under tensile loading with Figure 1.…”
Section: Introductionmentioning
confidence: 99%